Interpreting the actionable clinical role of rare variants associated with short QT syndrome - Estefanía Martínez-Barrios; Andrea Greco; José Cruzalegui; Sergi Cesar; Nuria Díez-Escuté; Patricia Cerralbo; Fredy Chipa; Irene Zschaeck; Leonel Slanovic; Alipio Mangas; Rocío Toro; Josep Brugada; et al. (Human Genetics, 2024)
Genetic testing is recommended in the diagnosis of short QT syndrome. This rare inherited lethal entity is characterized by structural normal hearts with short QT intervals in the electrocardiogram. Few families diagnosed with this arrhythmogenic disease have been reported worldwide so far, impeding a comprehensive understanding of this syndrome. Unraveling the origin of the disease helps to the early identification of genetic carriers at risk. However, only rare variants with a definite deleterious role should be actionable in clinical practice. Our aim was to perform a comprehensive update and reinterpretation, according to the American College of Medical Genetics and Genomics recommendations of all rare variants currently associated with short QT syndrome. We identified 34 rare variants. Reanalysis showed that only nine variants played a deleterious role associated with a definite short QT syndrome phenotype. These variants were located in the four main genes: KCNQ1 , KCNH2 , KCNJ2 or SLC4A3 . Additional rare variants located in other genes were associated with other conditions with phenotypic shortened QT intervals, but not definite diagnosis of short QT syndrome. Periodically updating of rare variants, especially those previously classified as unknown, helps to clarify the role of rare variants and translate genetic data into clinical practice.

Near-surface wind speed trends and variability over the Antarctic Peninsula, 1979–2022 - Miguel Andres-Martin; Cesar Azorin-Molina; Encarna Serrano; Sergi González-Herrero; Jose A. Guijarro; Shalenys Bedoya-Valestt; Eduardo Utrabo-Carazo; Sergio M. Vicente Serrano (Atmospheric Research, 2024)

Clinical impact of rare variants associated with inherited channelopathies: a 5-year update - Georgia Sarquella-Brugada; Anna Fernandez-Falgueras; Sergi Cesar; Elena Arbelo; Mónica Coll; Alexandra Perez-Serra; Marta Puigmulé; Anna Iglesias; Mireia Alcalde; Marta Vallverdú-Prats; Victoria Fiol; Carles Ferrer-Costa; et al. (Human Genetics, 2022)
A proper interpretation of the pathogenicity of rare variants is crucial before clinical translation. Ongoing addition of new data may modify previous variant classifications; however, how often a reanalysis is necessary remains undefined. We aimed to extensively reanalyze rare variants associated with inherited channelopathies originally classified 5 years ago and its clinical impact. In 2016, rare variants identified through genetic analysis were classified following the American College of Medical Genetics and Genomics’ recommendations. Five years later, we have reclassified the same variants following the same recommendations but including new available data. Potential clinical implications were discussed. Our cohort included 49 cases of inherited channelopathies diagnosed in 2016. Update show that 18.36% of the variants changed classification mainly due to improved global frequency data. Reclassifications mostly occurred in minority genes associated with channelopathies. Similar percentage of variants remain as deleterious nowadays, located in main known genes ( SCN5A, KCNH2 and KCNQ1 ). In 2016, 69.38% of variants were classified as unknown significance, but now, 53.06% of variants are classified as such, remaining the most common group. No management was modified after translation of genetic data into clinics. After 5 years, nearly 20% of rare variants associated with inherited channelopathies were reclassified. This supports performing periodic reanalyses of no more than 5 years since last classification. Use of newly available data is necessary, especially concerning global frequencies and family segregation. Personalized clinical translation of rare variants can be crucial to management if a significant change in classification is identified.

Effects of small hydropower plants on mercury concentrations in fish - Elaine C. Cebalho; Sergi Díez; Manoel dos Santos Filho; Claumir Cesar Muniz; Wilkinson Lázaro; Olaf Malm; Aurea R. A. Ignácio (Environmental Science and Pollution Research, 2017)